A Case of Quick Mummification: The Influence of Intrinsic and Extrinsic Factors in the Post Mortal Processes (Medico Legal Update, 2019)
After death, the corpse is subjected to many different post mortem phenomena that change the wholebiochemical and physical structures of the vital body. Those phenomena have different evolutions dependingon numerous factors typical of the death body and of the setting where the body lies. Mummification is oneof the special transformative process that consist in the drying of the entire body structures and requiresparticular wheatear condition and timing.